2022
DOI: 10.1080/02642069.2022.2026333
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual leadership and work alienation: analysis of mechanisms and constraints

Abstract: In the present study, we propose a negative association between spiritual leadership and work alienation and service employee social capital as a mediator of the spiritual leadership-work alienation link. We also hypothesize political skill as a boundary condition of the direct association between spiritual leadership and social capital and the indirect association between spiritual leadership and work alienation. Time-lagged (three rounds, three weeks apart) survey data collected from 283 service sector emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 81 publications
1
19
0
1
Order By: Relevance
“…In addition, the main cause of work alienation is that job cannot meet the needs and expectations of the individual (Yu et al, 2021). Existing research has demonstrated that spiritual and laissez-faire leadership in organizations are antecedents of job alienation (Usman et al, 2020;Ali et al, 2022). Research in this vein insinuates that interactive organizational factors (e.g., workplace incivility) are better predictors of alienation (DiPietro and Pizam, 2008).…”
Section: Workplace Incivility and Work Alienationmentioning
confidence: 99%
“…In addition, the main cause of work alienation is that job cannot meet the needs and expectations of the individual (Yu et al, 2021). Existing research has demonstrated that spiritual and laissez-faire leadership in organizations are antecedents of job alienation (Usman et al, 2020;Ali et al, 2022). Research in this vein insinuates that interactive organizational factors (e.g., workplace incivility) are better predictors of alienation (DiPietro and Pizam, 2008).…”
Section: Workplace Incivility and Work Alienationmentioning
confidence: 99%
“…Second, this study investigated the dual spiritual stimulation effect of perceived respect on innovation behavior, namely, the extrinsic motivation and moderating effect of spiritual leadership, as well as the internal psychological state and mediating effect of thriving at work. To date, scholars have mainly explored the influence and affecting mechanism of spiritual leadership on employees’ behavior ( Chen et al, 2019 ; Anser et al, 2021 ; Ali et al, 2022 ). Although studies have confirmed the moderating effect of some leadership styles such as transformational leadership ( Frieder et al, 2018 ; Meng et al, 2020 ), little attention has been paid to the moderating effect of spiritual leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual leadership, as an emerging paradigm in the broader research field of workplace spirituality, refers to a leadership style that stimulates and satisfies followers’ spiritual existence and spiritual needs (e.g., calling and membership) through intrinsic motivation ( Fry, 2003 ). Studies have demonstrated that spiritual leadership can meet followers’ spiritual needs by transmitting vision, faith, and altruistic love to them, which could influence their attitudes and behaviors ( Fry and Slocum, 2008 ; Fry and Kriger, 2009 ; Zou et al, 2020 ; Ali et al, 2022 ). People strive to be respected and valued in social relationships ( Bergsieker et al, 2010 ), and most employees expect to be treated with respect in the workplace ( Ng, 2016 ).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…At the same time, when the supervisor or organization assigns unreasonable tasks, employees can only accept those due to their subordinate status and the lack of their resources. In both cases, employees lack work autonomy and are powerless to change the outcome of their task assignment, thus becoming alienated from their work ( Ali et al, 2022 ).…”
Section: Research Hypothesismentioning
confidence: 99%